Análisis y elaboración de un plan de contingencia ante desastres utilizando estándar DRII para el área 2: bodega, informática, agua potable, registro de propiedad del centro de cómputo del gobierno municipal del cantón Camilo Ponce Enríquez de la provincia del Azuay - Jimbo Salinas, Mariuxi (2013)
It is shown that information and information systems are the most important assets available to most of the institutions. This means that the loss of this information could be a disaster for the company, thus losing customer data, business logic and a myriad of vital information, assuming irreparable damage to the company.